Direct Asymmetric Aldol Reaction in Continuous Flow Using Gel‐Bound Organocatalysts. Issue 17 (7th May 2021) - Schmiegel, Carsten J.; Baier, Rene; Kuckling, Dirk
Abstract: Continuous flow catalysis using a microfluidic reactor with gel‐bound proline organocatalysts is an attractive approach in organic synthesis due to interesting advantages such as the permanent production of catalyst‐free products and the easy product isolation by evaporation. Further advantages are the online detection of reactions and an adjustment of reaction parameters while the reaction is already running. Herein the formation of differently substituted aldol products within minutes at mild conditions in good to almost quantitative yields is described. The effects of different solvent mixtures and temperatures on the conversion and selectivity are analyzed in detail by NMR as well as the relationship between the height of the polymer structures and the conversion behavior of the asymmetric aldol reaction of 4‐nitrobenzaldehyde and cyclohexanone. The applicability of this system is demonstrated for a wide range of differently substituted nitrobenzaldehydes. It is shown that the described reactor setup delivers high conversion and good selectivity over up to 144 hours and that a highly reusable system was established. Abstract : The corresponding in‐depth analysis shows the general and extensive applicability of the MFR concept with an immobilized L‐proline‐based catalyst for carrying out asymmetric aldol reactions with various substrates. Using cyclohexanone and cyclopentanone as well as acetone, various ketones could be successfully converted as donors in the aldol reaction with various substituted aldehydes.